STUDENTS’ ANXIETY WHILE READING ALOUD DURING ENGLISH LEARNING AT THE TKJ ELEVENTH GRADE OF SMK NURUL YAQIN TLAGAH - B, Fitriyah; Rachmawati, Rina; Priastuti, Dyah Nugraheny (IKIP Widya Darma, 2023)
The objective of this study is to find out the factors causing students’ anxiety while reading aloud during English learning at the TKJ eleventh grade of SMK Nurul Yaqin Tlagah and to find out the teacher’s strategies to overcome the problems of students’ anxiety while reading aloud during English learning at the TKJ eleventh grade of SMK Nurul Yaqin Tlagah. This study uses a qualitative method. The subjects in this study were class 11 TKJ of SMK Nurul Yaqin Tlagah. Data was collected using interviews and observation to determine the factors causing students’ anxiety. The observation results showed that fear of making mistakes was the biggest factor causing students’ anxiety. Based on interviews, various factors of causing students’ anxiety while reading aloud during English learning. There are at least five factors found in this study: they feel that reading aloud in English learning is difficult, shyness and lack of confidence, fear of making mistakes, fear of being laughed at or mocked by their friends or classmates, and lack of vocabulary. In order to reduce the students’ anxiety, there are some strategies the teacher can apply while reading aloud during English learning. They are good preparation, positive thinking, building a good atmosphere while learning, peer groups, and using game methods while learning.